Tunnel-enlargement after MPFL reconstruction with a free gracilis graft does correlation with proximal tunnel malposition. Issue 4 (27th April 2017) - Turgay, Efe; Höger, Almut; Figiel, Jens; Roessler, Philip; Schüttler, Karl-Friedrich; Seif, Ali
Aims and Objectives: In current literature only one study investigates femoral tunnel enlargement after medial patello-femoral ligament (MPFL) reconstruction. Aim of the present study was to investigate the occurrence of femoral tunnel enlargement after MPFL reconstruction and a possible correlation to femoral tunnel position as well as clinical outcome. Materials and Methods: Patients with a minimum follow-up of at least 24 months after MPFL reconstruction with a free gracilis graft and without concomitant procedures were identified by reviewing patient files. Patients meeting the inclusion criteria were contacted and invited to participate in the study. After informed consent a clinical examination as well as magnetic resonance imaging (MRI) were performed. Tegner activity scale, Kujala score as well as the IKDC were evaluated. On MR images tunnel position in frontal and saggital planes, tunnel diameter as well as possible confounders such as cartilage damage were assessed. Results: 31 consecutive Patients (23 female, 8 male) were identified and took part in this ongoing investigation. Mean follow-up was 4.1 years. A femoral tunnel enlargement was noted in 12 patients. In 9 of these 12 patients the femoral tunnel was positioned too proximal. In the 19 patients that showed no tunnel enlargement only 6 tunnels were placed too proximal. Clinical results did not differ significantly between patient groups with or without tunnel enlargement regarding range of motion of the knee joint, Tegner, Kujala or IKDC score. Conclusion: Proximal malposition of the femoral tunnel was significantly more often in patients with femoral tunnel enlargement implying a biomechanical reason for tunnel enlargement after MPFL reconstruction. An impact on clinical outcome could not be perceived.